Electronic human resource management (E-HRM) and organisational performance in Bangladesh / Abdul Kadar Muhammad Masum - Abdul Kadar, Muhammad Masum (2017)
Electronic human resource management (E-HRM) is one of the strategic tools in organisations to achieve competitive advantage on processes and practices of human resource management (HRM). However, little research has been conducted on E-HRM implementation in developing countries. So, understanding influential factors involved in E-HRM usage at organisational level would be of benefit especially in developing countries such as Bangladesh. In seeking empirical evidence of E-HRM practices and its business implications, a multi-dimensional theoretical model known as the E-VALUE model was introduced. The E-VALUE model assessed the drivers of E-HRM usage by integrating the mature Technology-Organisation-Environment (TOE) framework and recently developed Human-Organisation-Technology (HOT-fit)-fit model to understand this issue. Human characteristic were represented by two independent variables namely senior executives’ characteristics and IT expertise of HR personnel. Technological characteristics were represented by four independent variables namely relative advantage, perceived compatibility, perceived complexity, and perceived cost. Organisational characteristics on the other hand, included three independent variables: top management support, organisational culture, and centralisation. Environmental characteristics were represented by competitive pressure and technology vendor support. In looking at the relationship between E-HRM usage and organisational performance, organisational performance was measured based on six non-financial measures i.e., effectiveness, efficiency, development, satisfaction, innovation, and quality. The E-VALUE model also tested the moderating influence of business experience wih E-HRM (in years) on the relationship between E-HRM usage and organisational performance (known as “E-HRM usage – organisational performance” relationship). Besides, the mediating effect of job satisfaction of HR personnel is also examined by measuring job satisfaction of HR personnel because of E-HRM implementation. The target population of E-HRM adopting companies in Bangladesh was unknown. Therefore, a variety of subsequent sources were utilised to make a complete list of E-HRM adopting companies following guidelines of past research. The questionnaire survey method was used in collecting primary data. Samples yielded 554 usable questionnaires from 138 organisations in Bangladesh. The structural equation modelling method was used to evaluate the model. In assessing the eleven drivers of E-HRM usage, only eight factors such as senior executives’ characteristics, IT expertise of HR personnel, perceived compatibility, perceived cost, top management support, organisational culture, centralisation, and competitive pressure were found to have significant influence on E-HRM usage. Next, E-HRM usage was found to have significant influence on organisational performance with positive relationship. Testing the moderator influence, businesss experience with E-HRM (in years), was found to moderate the relationship between E-HRM usage and organisational performance. In addition, in testing the mediation influence, job satisfaction of HR Personnel was found to partially mediate on the above mentioned relationship.This study contributes to the existing body of knowledge by enhancing current understanding of the organisational adoption of E-HRM and its impact on organisational performance, which is an under-researched area in Bangladesh as a developing country. The research results also revealed constructive suggestions to researchers, HR professionals, and the organisations to increase the likelihood of adopting E-HRM.